Corruption Plots : Stories, Ethics, and Publics of the Late Capitalist City - Ranganathan, Malini, 1979-; Doshi, Sapana, 1974-; Pike, David L. (David Lawrence), 1963- (Book collections on Project MUSE., 2023)
"With their skyscrapers, land grabs, and evictions invoking economic polarization, cities of the Global South provide charged settings for allegations of 'corruption.' Through interdisciplinary analysis, the authors argue that corruption is a storytelling practice about how states and elites abuse power in the making of unequal cities in late capitalism"--